Rom, musicisti sotterranei - Uboldi, Francesco (Italy : Francesco Uboldi, 2004)
Persecuted under Nicolae Ceausescu's regime, famished and humiliated, the Roma musicians never gave up pursuing a dream: to make a living out of their music. They came to Milan without work and started playing in the streets and subways, eternally suspended between life in a caravan and the mirage of a heated house. Nonetheless, they stayed cheerful and tried to make it in their adoptive country.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films